(3QSGdI GdHfGJ GdUZjQIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdEdg GdMGce GdefRg GdeYHhO hTcQJ YHOg GdbGFe HGdjhe GdehYhO jG CjJgG GdHfGJ GdZGadGJ GdfGSjGJ ddMb GdeOYjGJ s
(3BNQgG (B:s
(3hjMd GdYPGH hGdSNW Ydi GdfGcKjf GdeHGgJjf heG Ydi GdQShd GdSGOb Shi GdHdGZ GdeHjf hGdMeO dEdg GdYGdejf hGdTcQ dhdjg YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B83s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds